A Comparative Study Between Amniotic Membrane and Hydrocolloid in the Healing of Partial Thickness Burn Wounds - Farhana, Fatima; Majumder, Sharif Muhammad Mahmudul Hasan (Journal of Comilla Medical College Teachers’ Association, 2024)
Background: Management of partial thickness burn wounds is mostly conservative, and rapid wound healing is desirable to obtain a good functional and cosmetic outcome. Wound dressing materials play an important role in maintaining an optimal wound milieu and avoiding complications from delayed healing. Methods: From January 2018 to December 2018, the study was conducted as a clinical trial over 100 patients at Dhaka Medical College Hospital. The patients who sustained partial thickness burn < 15% TBSA were included in the study, equally allocated between two (2) comparison groups (Group A: amniotic membrane and Group B: hydrocolloid), and the clinical efficacy and functionality of the two groups regarding the rapidity of wound healing, frequency of dressing changes, requirement of analgesics, rate of infections, and need for a skin graft were assessed. Results: Hydrocolloid dressing showed a shorter healing time (p<0.002), less frequent dressing change (p<0.001), lower requirements of pain medication (p<0.001), and improved patients comfort which were statistically significant. Conclusion: Amniotic membrane showed comparable clinical and functional efficacy with hydrocolloid in burn wound healing, with superior healing time and comfort in favor of the later. J Com Med Col Teachers Asso July 2024; 28(2): 58-64